2014
DOI: 10.1016/j.ijsu.2014.01.010
|View full text |Cite
|
Sign up to set email alerts
|

Impact of intra-abdominal fat on surgical outcome and overall survival of patients with gastric cancer

Abstract: Obesity, as represented by BMI and VFA, may not be a poor prognostic factor in patients with gastric cancer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
15
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(22 citation statements)
references
References 15 publications
5
15
1
Order By: Relevance
“…Furthermore, the amount of perirenal fat has been identified as a marker for intraabdominal fat and was associated with postoperative complications in elective colorectal surgery . In conjunction with results from this study another study in gastric cancer surgery patients also did not show differences in outcome in association with visceral adipose tissue .…”
Section: Discussionsupporting
confidence: 82%
“…Furthermore, the amount of perirenal fat has been identified as a marker for intraabdominal fat and was associated with postoperative complications in elective colorectal surgery . In conjunction with results from this study another study in gastric cancer surgery patients also did not show differences in outcome in association with visceral adipose tissue .…”
Section: Discussionsupporting
confidence: 82%
“…As reported in a study of 46 patients with advanced ovarian cancer, the amount of VAT cross-sectional area was not related to PFS or OS, regardless of treatment type (Slaughter et al, 2014). A study in patients with gastric adenocarcinoma who received gastrectomy also reported no association between VAT cross-sectional area and post-surgical OS (Kim et al, 2014). Conversely, Li et al (2015) found that higher VAT, measured by intraperitoneal adipose tissue thickness, was associated with shorter OS (p = .003) and DFS (p < .001) in patients with locally advanced gastric cancer.…”
Section: Other Cancer Types: Ovarian Gastric Adrenocortical Softmentioning
confidence: 74%
“…Among the studies hereby reviewed, VAT cross-sectional area was the most commonly used index, measured in 14 studies (Gaujoux et al, 2012;Guiu et al, 2010;Kaneko et al, 2015;Kang et al, 2012;Kim, Chin, Hwang, & Jun, 2014;Ladoire et al, 2011;Lee, Jeong et al, 2015;Lee, Murphy et al, 2015;Nault et al, 2015;Naya et al, 2010;Pecorelli et al, 2016;Slaughter et al, 2014;Steffens et al, 2011;Yamamoto et al, 2012). The distance or thickness between kidney and abdominal wall musculature at the level of renal vein has been used as a proxy for quantifying VAT in seven studies (Balentine, Enriquez et al, 2010;Clark et al, 2013;Li et al, 2015;Mathur et al, 2011;Miller et al, 2012;Papoulas et al, 2015;Pausch et al, 2012), by virtue of measurement efficiency and convenience.…”
Section: Methodological Considerationsmentioning
confidence: 99%
“…Much of the research on surgical treatment of gastric cancer has focused on obesity in recent years (1)(2)(3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13). Obesity is associated with increased blood loss, a prolonged operative time, a high rate of postoperative complications, and inadequate lymph node staging.…”
Section: Introductionmentioning
confidence: 99%